2023
DOI: 10.1002/adma.202210776
|View full text |Cite
|
Sign up to set email alerts
|

RNA‐Targeting Carbon Dots for Live‐Cell Imaging of Granule Dynamics

Abstract: It is significant to monitor the different RNA granules dynamics and phase separation process inside cells under various stresses, for example, oxidative stress. The current small‐molecule RNA probes work well only in fixed cells and usually encounter problems such as insufficient stability and biocompatibility, and thus a specific RNA‐targeting fluorescent nanoprobe that can be used in the living cells is urgently desired. Here, the de novo design and microwave‐assisted synthesis of a novel RNA‐targeting, red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 59 publications
1
30
0
Order By: Relevance
“…Bi et al reported a microwaveassisted synthesis route for a red-emissive, RNA-targeting CD (named as M-CDs) using neutral red and levofloxacin as the precursors. 31 The M-CDs possessed a high fluorescence quantum yield of 22.83% and could bind to RNA selectively which lead to stronger red fluorescence. In addition, M-CDs could enter cells within 5 s and thus could be used for real-time tracing of the dynamic process of intracellular stress granules under oxidative stress.…”
Section: Fluorescence Imagingmentioning
confidence: 99%
“…Bi et al reported a microwaveassisted synthesis route for a red-emissive, RNA-targeting CD (named as M-CDs) using neutral red and levofloxacin as the precursors. 31 The M-CDs possessed a high fluorescence quantum yield of 22.83% and could bind to RNA selectively which lead to stronger red fluorescence. In addition, M-CDs could enter cells within 5 s and thus could be used for real-time tracing of the dynamic process of intracellular stress granules under oxidative stress.…”
Section: Fluorescence Imagingmentioning
confidence: 99%
“…12,13 Researchers have developed CDs with special functions for targeting membrane lipids, proteins, ligands and biomarkers in a variety of cells. 14–16…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Researchers have developed CDs with special functions for targeting membrane lipids, proteins, ligands and biomarkers in a variety of cells. [14][15][16] Lysosomes in immune cells are involved in killing foreign pathogens and abnormal proteins in their own cells, and they are also involved in the growth process of tumour cells. [17][18][19] Therefore, monitoring the physiological state of intracellular lysosomes is of interest for studies related to cell biology.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon dots (CDs) are carbon nanoparticles that have emerged as promising photosensitizer agents due to their numerous merits including easy preparation, excellent biocompatibility, good water dispersibility, and rich photophysical properties. Moreover, the surface state of CDs could be readily tuned by elaborate choice of the starting materials or postmodification, endowing their targeting capability to specific organelles or components. Among them, ribonucleic acid (RNA), which plays active roles in the coding, regulation, and expression of genes, represents an efficient and ideal target site in various therapeutic modalities on account of its poor tolerance to ROS. To date, there are a few reports on the synthesis of RNA or nucleolus-targeted CDs. For example, Lin and Wu et al demonstrated the potential of CDs in drug delivery by advantage of their effective accumulation in nucleolus. Very recently, our group reported the rational design of RNA-targeting CDs for dynamic imaging of stress granules based on levofloxacin as it is an antibiotic that works by relying on the high binding affinity between levofloxacin and nucleic acids . However, the individual CDs hardly produce ROS, and thus, additional conjugation of drug or photosensitizer is required for treatment.…”
mentioning
confidence: 99%
“…40−42 Very recently, our group reported the rational design of RNAtargeting CDs for dynamic imaging of stress granules based on levofloxacin as it is an antibiotic that works by relying on the high binding affinity between levofloxacin and nucleic acids. 43 However, the individual CDs hardly produce ROS, and thus, additional conjugation of drug or photosensitizer is required for treatment. Wei et al reported the first nucleolus-targeting CDs which can be directly used for PDT, while the ROS quantum yield (4.8%) was far from satisfactory.…”
mentioning
confidence: 99%